2015
DOI: 10.1016/j.bandl.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lexical statistics on temporal lobe cortical dynamics during spoken word listening

Abstract: Neural representations of words are thought to have a complex spatio-temporal cortical basis. It has been suggested that spoken word recognition is not a process of feed-forward computations from phonetic to lexical forms, but rather involves the online integration of bottom-up input with stored lexical knowledge. Using direct neural recordings from the temporal lobe, we examined cortical responses to words and pseudowords. We found that neural populations were not only sensitive to lexical status (real vs. ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 47 publications
1
33
0
1
Order By: Relevance
“…Finally, recent work has also demonstrated that distributed cortical networks encode abstract statistical information about lexical and other linguistic features, including lexical frequency (Cibelli, Leonard, Johnson, & Chang, 2015; Leonard, Bouchard, Tang, & Chang, 2015). These studies challenge the notion of a ‘mental lexicon’ that is simply a dictionary of all known words (Gow Jr, 2012; Ullman et al, 1997), and provide evidence that many aspects of speech processing including acoustic-phonetic, phonemic, and lexical processing are deeply influenced by language statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent work has also demonstrated that distributed cortical networks encode abstract statistical information about lexical and other linguistic features, including lexical frequency (Cibelli, Leonard, Johnson, & Chang, 2015; Leonard, Bouchard, Tang, & Chang, 2015). These studies challenge the notion of a ‘mental lexicon’ that is simply a dictionary of all known words (Gow Jr, 2012; Ullman et al, 1997), and provide evidence that many aspects of speech processing including acoustic-phonetic, phonemic, and lexical processing are deeply influenced by language statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in the fields of cognitive neuroscience of language, psycholinguistics, neurolinguistics, and experimental psychology can use it to create stimuli representative of the spoken language-both sublexical (e.g., syllable) and lexical (word) stimuli-controlled for normalized frequency, transition probabilities, or mutual information. Given the known effects of distributional statistics on speech perception and production, behaviorally and at the neural level (Carreiras, Mechelli, & Price, 2006;Carreiras & Perea, 2004;Cibelli, Leonard, Johnson, & Chang, 2015;Deschamps et al, 2016;Karuza et al, 2013;Leonard et al, 2015;Newport & Aslin, 2004;Pelucchi et al, 2009aPelucchi et al, , 2009bPeña et al, 2002;Saffran et al, 1996;Saffran, Johnson, Aslin, & Newport, 1999;Tremblay et al, 2012;Tremblay et al, 2016;Vitevitch, 2003;Vitevitch & Luce, 1998;Vitevitch et al, 1997Vitevitch et al, , 1999 it is important to control for these effects in order to avoid confounds that can mask other effects of interest, such as articulatory or phonological complexity. However, such important experimental control is only possible when databases providing this information exist, which was not the case for Quebec spoken French.…”
Section: Resultsmentioning
confidence: 99%
“…6-11) and word-level processes (e.g., refs. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. However, the most distinctive feature of human language is its compositionality: the ability to create and understand complex meanings from novel combinations of words structured into phrases and sentences (27).…”
mentioning
confidence: 99%